(untitled) (Faridpur Medical College Journal, 2020)
Viral encephalitis remains a significant public health problem worldwide including Bangladesh. The recommended treatment for herpes simplex encephalitis (HSE) remains intravenous acyclovir. In resource-poor countries, however, intravenous formulations are usually unavailable or unaffordable. Efficacy of treatment depends upon cerebrospinal fluid (CSF) level of acyclovir. Main concern of use of valacyclovir is central nervous system penetration of drugs. This study reports the comparison of penetration of acyclovir into the cerebrospinal fluid (CSF) in patients with HSE, treated with the oral pro drug valacyclovir at a dose of 1,000 mg three times daily. The oral therapy achieved adequate acyclovir concentrations in the CSF and may be an acceptable early treatment for suspected HSE in resource-limited settings. In our country treatment of HSE by IV acyclovir is costly and needs about 45000 BDT per person to complete treatment and is not available in rural areas, on the other hand it is 10 times cost effective in treatment with oral Valacyclovir. Faridpur Med. Coll. J. Jan 2019;14(1): 41-43